Evolutionary design with freedom-Fin shapes and entrance length channels for heat sinks - Bejan, A.; Almahmoud, H.; Gunes, U. (PERGAMON-ELSEVIER SCIENCE LTD, 2023)
The new direction traced in this article is to vary freely and simultaneously the fin and flow channel aspect ratios in the search for the complete high-density heat transfer flow architecture. We show that when the combined solid and fluid volume is specified, and the fluid flow rate is known, it is possible to anticipate from theory the complete design (all the aspect ratios) of the flow configuration. The power to predict covers the overall heat transfer rate and the required pumping power. The configuration and performance owe their existence to the multiple degrees of freedom identified in the design, and exploited in the theory.
Keywords: Evolutionary design; Freedom; Constructal; Fins; Entrance length; Heat sink; CONSTRUCTAL THEORY; TREES; Thermodynamics; Mechanics